Plant defense against herbivores: chemical aspects - Mithöfer, Axel; Boland, Wilhelm (Annual review of plant biology, 2012)
Plants have evolved a plethora of different chemical defenses covering nearly all classes of (secondary) metabolites that represent a major barrier to herbivory: Some are constitutive; others are induced after attack. Many compounds act directly on the herbivore, whereas others act indirectly via the attraction of organisms from other trophic levels that, in turn, protect the plant. An enormous diversity of plant (bio)chemicals are toxic, repellent, or antinutritive for herbivores of all types. Examples include cyanogenic glycosides, glucosinolates, alkaloids, and terpenoids; others are macromolecules and comprise latex or proteinase inhibitors. Their modes of action include membrane disruption, inhibition of nutrient and ion transport, inhibition of signal transduction processes, inhibition of metabolism, or disruption of the hormonal control of physiological processes. Recognizing the herbivore challenge and precise timing of plant activities as well as the adaptive modulation of the plants' metabolism is important so that metabolites and energy may be efficiently allocated to defensive activities.